2021
DOI: 10.1158/2159-8290.cd-20-0818
|View full text |Cite
|
Sign up to set email alerts
|

Genetically Defined Syngeneic Mouse Models of Ovarian Cancer as Tools for the Discovery of Combination Immunotherapy

Abstract: have patents pending. P.T.H. is a co-founder and member of the Board of Directors of LayerBio, Inc. She is on the Scientific Advisory Board of Moderna, Inc. and the Board of Directors of Alector, Inc., and she receives consulting fees and holds equity in these companies. P.T.H. is not aware of any conflicts of interest concerning the manuscript's content and topic and these entities. B.G.N. is a cofounder, holds equity in, and is a member of the Scientific Advisory Board at Navire Pharmaceuticals. He also has … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
83
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 90 publications
(90 citation statements)
references
References 80 publications
7
83
0
Order By: Relevance
“…Consistent with previous observations from syngeneic mouse models 7 , the BRCA1/2mut tumors contained an increased infiltration of IBA1+ and M2-type IBA1+CD163+ and CD163+ macrophages, whereas the HRwt tumors had abundant CD11c+ myeloid cells. The myeloid cells also showed abundant and distinct PD-L1 expression profiles between the HR genotypes, with the highest expression in the CD11c+ cells in the BRCA1/2mut tumors and M2-type macrophages in the HRwt tumors.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Consistent with previous observations from syngeneic mouse models 7 , the BRCA1/2mut tumors contained an increased infiltration of IBA1+ and M2-type IBA1+CD163+ and CD163+ macrophages, whereas the HRwt tumors had abundant CD11c+ myeloid cells. The myeloid cells also showed abundant and distinct PD-L1 expression profiles between the HR genotypes, with the highest expression in the CD11c+ cells in the BRCA1/2mut tumors and M2-type macrophages in the HRwt tumors.…”
Section: Discussionsupporting
confidence: 91%
“…Notably, preliminary evidence suggests that HR-deficient tumors have a distinct tumor-immune microenvironment 6,7 . BRCA1/2mut tumors have been predicted to contain more neoantigens than tumors with no alterations in genes of the HR pathway (HRwt) 6 , harbor an increased number of tumor infiltrating lymphocytes 6 , and have an elevated PD-L1 expression as compared to HR-proficient tumors 6 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, this suppression of p53 and overexpression of AKT and c-Myc are able to overcome immunosurveillance and induce peritoneal tumors in immunocompetent mice too. Similarly, Sonia Iyer and colleagues constructed cell lines combining loss of Trp53 and overexpression of Ccne1, Akt2, and Trp53 R172H , and driven by KRAS G12V (KPCA) or Brd4 (BPCA) or Smarca4 (SPCA) overexpression [84]. Thus, this model represents an excellent and reliable platform for preclinical and translational PCa research and, more interestingly, the testing of immunotherapeutic agents.…”
Section: Pca Genetically Induced Modelsmentioning
confidence: 99%
“…Using these syngeneic organoid models, they demonstrated that tumors with Tp53 -/-/Ccne1 OE /Akt2 OE /Kras OE genotype were highly sensitive to chemotherapy and immunotherapy combinations (gemcitabine plus anti-PD-L1 and anti-CTLA-4), while Tp53 -/-/Pten -/-/Nf1 -/tumors were not [7]. Similarly, the Weinberg group also demonstrated the utility of engineering ex vivo murine FTE cells bearing complex mutational combinations (up to five co-occurring genetic alterations) and forming a panel of five genotypespecific models that grew in syngeneic hosts [9]. By treating these new mouse models with a combination of immune checkpoint inhibitors and chemotherapies, they identified follistatin as a driver of resistance to immune checkpoint inhibitors in Ccne1-overexpressing (Ccne1 OE ) mice [9].…”
Section: Next Generation Mouse Models Of Squamous Cell Lung Cancer Fomentioning
confidence: 99%
“…Similarly, the Weinberg group also demonstrated the utility of engineering ex vivo murine FTE cells bearing complex mutational combinations (up to five co-occurring genetic alterations) and forming a panel of five genotypespecific models that grew in syngeneic hosts [9]. By treating these new mouse models with a combination of immune checkpoint inhibitors and chemotherapies, they identified follistatin as a driver of resistance to immune checkpoint inhibitors in Ccne1-overexpressing (Ccne1 OE ) mice [9].…”
Section: Next Generation Mouse Models Of Squamous Cell Lung Cancer Fomentioning
confidence: 99%